A Systematic Review of Parenting Scales Measurement Invariance/ Equivalence of by Race and Ethnicity: Recommendations for Inclusive Parenting Research. (January 2023) - Rodriguez, Violeta J.; La Barrie, Dominique L.; Zegarac, Miriam C.; Shaffer, Anne
The limited inclusion of racial/ethnic minorities in the development and validation of parenting measures limits our understanding of whether parenting constructs are valid in racial and ethnic minorities. Tests of measurement invariance/equivalence (MI/E) of parenting measures can help evaluate the validity of parenting constructs among racial/ethnic minorities. This systematic review summarized studies on MI/E of parenting constructs by race/ethnicity and evaluated the strength of the evidence. A literature search was conducted using various databases and references to retrieve studies from the United States. Indeed, 10 studies were identified that tested for MI/E of eight parenting scales by race/ethnicity. Only one scale showed moderate evidence of MI/E, five showed weak evidence of MI/E, and two showed no evidence of MI/E. Most studies (80%) used factor analytic methods to test for MI/E, but only two studies (20%) examined all levels of invariance. These findings show that differences exist in how racial/ethnic minorities perceive parenting constructs. Further research is needed to develop more inclusive parenting measures, to protect against the ways in which biased measures may pathologize or misrepresent parenting practices among racial/ethnic minorities.